FREGAT: an R package for region-based association analysis. (24th March 2016) - Belonogova, Nadezhda M.; Svishcheva, Gulnara R.; Axenovich, Tatiana I.
Abstract : Summary: Several approaches to the region-based association analysis of quantitative traits have recently been developed and successively applied. However, no software package has been developed that implements all of these approaches for either independent or structured samples. Here we introduce FREGAT (Family REGional Association Tests), an R package that can handle family and population samples and implements a wide range of region-based association methods including burden tests, functional linear models, and kernel machine-based regression. FREGAT can be used in genome/exome-wide region-based association studies of quantitative traits and candidate gene analysis. FREGAT offers many useful options to empower its users and increase the effectiveness and applicability of region-based association analysis. Availability and Implementation: https://cran.r-project.org/web/packages/FREGAT/index.html Supplementary Information: Supplementary data are available at Bioinformatics Online. Contact: belon@bionet.nsc.ru